Assembly patterns and functional diversity of tree species in a successional gradient of Araucaria forest in Southern Brazil - Vicente-Silva, José; Bergamin, Rodrigo S.; Zanini, Kátia J.; Pillar, Valério D.; Müller, Sandra C. (Natureza & conservação, 2016)
Functional analysis of secondary succession may allow identifying and predicting processes of community assembly, which can be simultaneously driven by factors related to ecological filters and neutral forces. This study evaluated trait-convergence assembly patterns and trait-divergence assembly patterns in successional areas of Araucaria forest. Plant species were sampled in both the upper and lower strata and were described by 15 functional traits. Data analyses were based on multiplication and Procrustes adjustment of matrices, which permit to discriminate trait-convergence assembly patterns and trait-divergence assembly patterns along the forest succession (our environmental variable), and the influence of phylogeny on these patterns. Initial and late forests were highly different in species composition, but the regenerating stratum was already more similar especially in functional terms. Traits related to the acquisitive-conservative trade-off (wood density, leaf nitrogen content, leaf area, leaf dry matter content) revealed strong convergent patterns of successional changes. Moreover divergence was maximized by specific leaf area, seed mass, deciduousness, and dispersal mode, showing a higher functional diversity in late Araucaria forests.